2017
DOI: 10.1089/vim.2017.0030
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of HCV RNA and NS5A Protein in Peripheral Blood Mononuclear Cells Is a Prognostic Tool for Sustained Virological Response

Abstract: Hepatitis C Virus (HCV) infection is a major health concern worldwide. The presence of both HCV viral RNA and NS5A proteins in peripheral blood mononuclear cells (PBMCs) indicate the efficacy of the treatment during sustained virological response (SVR) and end of treatment response (ETR). The main objective of this study was to detect the absence or presence of HCV RNA and NS5A proteins in PBMCs. Blood samples were taken from selected patients (Islamabad, Pakistan) before treatment, at ETR, and during SVR. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…HCV targets the liver as a primary site of infection, but the past reports have shown that it also infects the PBMCs to a lesser extent [39,40]. The HCV infection of PBMC could be a reservoir for the relapse after treatment and a source of resistance to the antiviral treatment [41,42]. Furthermore, testing the PBMCs for the specific detection of (+) and (−) strands of HCV RNA will shed light on the infection status as the (−) strand is formed only during the virus replication step in an ongoing infection.…”
Section: Quantification Of Positive (+) and Negative (−) Strand Hcv R...mentioning
confidence: 99%
“…HCV targets the liver as a primary site of infection, but the past reports have shown that it also infects the PBMCs to a lesser extent [39,40]. The HCV infection of PBMC could be a reservoir for the relapse after treatment and a source of resistance to the antiviral treatment [41,42]. Furthermore, testing the PBMCs for the specific detection of (+) and (−) strands of HCV RNA will shed light on the infection status as the (−) strand is formed only during the virus replication step in an ongoing infection.…”
Section: Quantification Of Positive (+) and Negative (−) Strand Hcv R...mentioning
confidence: 99%